Psychometric Analysis of a Measure of Spiritual Experiences in Peruvian Adults - Morales-García, Wilter C. (Journal of psychology and theology, 2023)
Research on spirituality has increased considerably in the last decade.This study analyzes the psychometric properties of the Daily Spiritual Experience Scale (DSES) in a Peruvian sample.The study had a cross-sectional design. The population was Peruvian adults with ages ranging between 18 and 70 years (M = 30.60, SD = 11.22) recruited through nonprobabilistic sampling. The confirmatory factor analysis (CFA) was performed. Internal consistency was assessed by Cronbach’s alpha (α), McDonalds’ omega (ω), and H-coefficient (H).The structure of 16 items was not confirmed. A 13-item DSES unidimensional model was suggested (χ2 = 184.78, df = 65; confirmatory fit index [CFI] = 0.92, Tucker–Lewis index [TLI] = 0.91, root mean square error of approximation [RMSEA] = 0.08, standardized root mean square residuals [SRMR] = 0.04) and the DSES-6 model (χ2 = 9.570, df = 9; CFI = 1.00, TLI = 1.00, RMSEA = 0.02, SRMR = 0.02) and its reliability had excellent values. Concurrent validity with measures of anxiety and depression were evidenced.The DSES-13 and DSES-6 versions are valid and reliable instruments to evaluate spiritual experiences in the Peruvian context.